Konsep Kepemimpinan dalam Pendidikan Menurut Ki Hadjar Dewantara - S, Siti Munawira; Salam, Ifriani Abdul; Oktaviana, Wahidah; Rama, Bahaking (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Leadership is something that is quite dynamic and evolves over time. Many have put forward their ideas about leadership. One of them is the concept of leadership put forward by Ki Hadjar Dewantara which includes 3 aspects that are independent and interrelated. This management concept does not differentiate people based on their levels, but rather based on their roles. This role can be front, middle, and back. In the sense that the leader must be able to adapt to the situation, sometimes the leader’s role is in front (leading, directing and directing), sometimes his role is in the middle (mediator, being neutral and impartial) and sometimes behind (to support, encourage and give freedom to members to be creative according to their respective talents). This article discusses the concept of leadership according to Ki Hadjar Dewantara, the influence and strategies that can be done in applying this concept.